Association between age and overall survival of patients with hepatocellular carcinoma after hepatic resection. Issue 8 (16th September 2016) - Tan, Jun‐Tao; Zhao, Chang; Peng, Ning‐Fu; Yang, Yang; Zhong, Jian‐Hong; Yang, Tian; Zheng, Ming‐Hua; Wang, Yan‐Yan; Gong, Wen‐Feng; Xiang, Bang‐De; Li, Le‐Qun
Abstract : Aim: The suitability of hepatic resection for older patients remains controversial. This study aimed to investigate whether age influences overall survival of patients with hepatocellular carcinoma (HCC) after resection. Methods: Records of 1, 132 patients with HCC after hepatic resection were retrospectively reviewed. Overall survival (OS) was compared between younger and older patients based on five cut‐off ages (30, 40, 50, 60, and 70 years). Results: Across all patients, OS was 89.7% at 1 year, 67.7% at 3 years, and 47.7% at 5 years. OS was similar between younger and older patients at all cut‐off ages (all P > 0.1), but OS was marginally lower among patients >70 years old than those ≤70 ( P = 0.090). Multivariate analyses identified several risk factors for lower OS: preoperative serum albumin <35 g/L, alanine aminotransferase >80 U/L, α‐fetoprotein ≥400 ng/ml, presence of esophagogastric varices or macrovascular invasion, incomplete/absent tumor capsule, tumor size >10 cm, tumor number ≥3, and major hepatectomy. Conclusion: Age does not influence the prognosis of patients with HCC after hepatic resection. Older patients should be considered for curative resection if remnant liver volume and liver function are adequate. J. Surg. Oncol. 2016;114:966–970 . © 2016 Wiley Periodicals, Inc.